Freshwater macroinvertebrate traits assessment as complementary to taxonomic information for mining impact detection in the northern Peruvian Andes - Mercado-Garcia, D. (2022)
Aim: We studied the distribution of freshwater macroinvertebrate taxa and traits to distinguish ecological gradients among the mining- controlled and natural headwaters, and rural and urban economic activity influences. Location: In 2016’s dry season, macroinvertebrate samples were collected at 40 loca tions in the Mashcon watershed, northern Peruvian Andes. Six locations were in the headwaters directly influenced by mining, eight near- pristine tributary headwaters, 14 agricultural locations at midstream and 12 urban locations downstream. Methods: Eight traits (five biological and three ecological) were selected according to data availability, and modalities scores were assigned using the weighted and the dominant- trait approaches. The traits relative abundances and abiotic conditions were compared among watershed sections. The ecological interpretability of the un grouped data was verified with a distance- based redundancy analysis. Results: The high- altitude mining section had fewer taxa types and abundance, and distinct body forms distributions and prevalent body sizes in macroinvertebrate com munities, relatable to the control of the mining headwaters. Physiological and ecologi cal traits (respiration, mobility and attachment, food sources, feeding habits, saprobity and pH preferenda) differed among traits quantification approaches and were less informative at high altitudes. The ecological conditions from the near- pristine trib utaries recovered in the vegetated midstream section, to again be affected in the downstream urban section. Main Conclusions: Our results suggest the presence of ecological impairment despite the excellent physicochemical quality of the water discharged by the mine. The ob tainment of autecological information at a higher taxonomic resolution, e.g. for ubiq uitous taxa like Acari and Chironomidae, would be needed to advance the freshwater quality assessment of ecologically and hydrogeochemically complex Andean mining ecosystems.